2021
DOI: 10.1371/journal.pone.0258689
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients in platform C19, a COVID-19 research database combining primary care electronic health record and patient reported information

Abstract: Background Data to better understand and manage the COVID-19 pandemic is urgently needed. However, there are gaps in information stored within even the best routinely-collected electronic health records (EHR) including test results, remote consultations for suspected COVID-19, shielding, physical activity, mental health, and undiagnosed or untested COVID-19 patients. Observational and Pragmatic Research Institute (OPRI) Singapore and Optimum Patient Care (OPC) UK established Platform C19, a research database c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The OPC QI programme in primary care involves a combined review of de-identified EMRs; patients’ responses to disease-specific questionnaires; provision of tailored reports to practices with risk stratification and best-practice support patient management; education workshops, implementation programmes and innovation. 17 The program supports remote patient reviews by completion of key questionnaires that can either replace consultations and QOF reviews or make them easier to deliver by completing pre- (remote) consultation work.…”
Section: Results and Findings To Datementioning
confidence: 99%
“…The OPC QI programme in primary care involves a combined review of de-identified EMRs; patients’ responses to disease-specific questionnaires; provision of tailored reports to practices with risk stratification and best-practice support patient management; education workshops, implementation programmes and innovation. 17 The program supports remote patient reviews by completion of key questionnaires that can either replace consultations and QOF reviews or make them easier to deliver by completing pre- (remote) consultation work.…”
Section: Results and Findings To Datementioning
confidence: 99%
“…Appropriate platforms for shared access to routine data have been developed in various countries, although only a few national solutions have emerged. In the United Kingdom, for example, the platform OpenSAFELY, the COVID-19 Research Platform, 4 or C19, a COVID-19 research database, 5 combining primary care electronic health record and patient reported information. In Germany, too, a national research data platform called “CODEX, Covid-19 Data Exchange Platform,” 6 is to be developed within the German “Network University Medicine (NUM)” 7 that will make data available to researchers nationwide in a standardized manner and in compliance with data protection laws.…”
Section: Background and Significancementioning
confidence: 99%